Characterization of the mitochondrial genome of Tetrastichus howardi (Olliff 1893) (Hymenoptera: Eulophidae) - Xue Tang; Baoqian Lyu; Hui Lu; Jihong Tang; Rui Meng; Bo Cai (Mitochondrial DNA. Part B. Resources, 2021)
The mitochondrial genome has been widely used in the study of phylogeny and species-level evolution. Here, we sequenced and analyzed the full mitogenome of Tetrastichus howardi, an important natural enemy of many lepidopteran pests. The complete mitochondrial genome has 14,791 nucleotides, containing 13 protein-coding genes (PCGs), 2 ribosomal RNA genes (rRNAs), 22 transfer RNA genes (tRNAs), and a partial control region. All the 13 PCGs started with typical ATN (ATA, ATG, and ATT) codon. Among 13 PCGs, nine genes terminated with the stop codon TAA and four genes terminated with T. Our study provides information on comparative mitogenomics of Eulophidae.